Advances in Human Error, Reliability, Resilience, and Performance Proceedings of the AHFE 2018 International Conference on Human Error, Reliability, Resilience, and Performance, July 21-25, 2018, Loews Sapphire Falls Resort at Universal Studios, Orlando, Florida, USA - Boring, Ronald L. (Advances in Intelligent Systems and Computing,, 2019)
This book brings together studies broadly addressing human error from different disciplines and perspectives. It discusses topics such as human performance; human variability and reliability analysis; medical, driver and pilot error, as well as automation error; root cause analyses; and the cognitive modeling of human error. In addition, it highlights cutting-edge applications in safety management, defense, security, transportation, process controls, and medicine, as well as more traditional fields of application. Based on the AHFE 2018 International Conference on Human Error, Reliability, Resilience, and Performance, held on July 21-25, 2018, in Orlando, Florida, USA, the book includes experimental papers, original reviews, and reports on case studies, as well as meta-analyses, technical guidelines, best practice and methodological papers. It offers a timely reference guide for researchers and practitioners dealing with human error in a diverse range of fields.